We do not know what we see; we see what we believe. Perceptions, emotions and reactions to campaign stimuli in the 2018 presidential election in Mexico. - Bárcena Juárez, Sergio Arturo (2019)
Can political ads produce enough emotional shock as for orienting a person’s vote? To answer this inquiry we monitored a group of first-time voters from different universities in Mexico City during the 2018 electoral process. Through association analysis and multidimensional scaling techniques, we contrasted their emotional response to campaign ads of the three main presidential candidates with their final vote on July 1st. Our results show there is only a slight correlation between emotional reaction to political ads and the vote cast by individuals. Emotions motivated by audiovisual stimuli, have a limited effect over vote orientation, since these reactions depend upon the interpretive capitals that each voter possesses.